Liquid embolic agents for endovascular embolization: evaluation of an established (onyx) and a novel (PHIL) embolic agent in an in vitro AVM model - Vollherbst, Dominik; Sommer, Christof-Matthias; Ulfert, Christian; Pfaff, Johannes; Bendszus, Martin; Möhlenbruch, Markus Alfred (American journal of neuroradiology, 2017)
BACKGROUND AND PURPOSE: Embolization plays a key role in the treatment of arteriovenous malformations. The aim of this study was to evaluate an established (Onyx) and a novel (precipitating hydrophobic injectable liquid [PHIL]) liquid embolic agent in an in vitro AVM model. MATERIALS AND METHODS: An AVM model was integrated into a circuit system. The artificial nidus (subdivided into 28 honeycomb-like sections) was embolized with Onyx 18 (group Onyx; n = 8) or PHIL 25 (group PHIL; n = 8) with different pause times between the injections (30 and 60 seconds, n = 4 per study group) by using a 1.3F microcatheter. Procedure times, number of injections, embolization success (defined as the number of filled sections of the artificial nidus), volume of embolic agent, and frequency and extent of reflux and draining vein embolization were assessed. RESULTS: Embolization success was comparable between Onyx and PHIL. Shorter pause times resulted in a significantly higher embolization success for PHIL (median embolization score, 28 versus 18; P = .011). Compared with Onyx, lower volumes of PHIL were required for the same extent of embolization (median volume per section of the artificial nidus, 15.5 versus 3.6 μL; P < .001). CONCLUSIONS: While the embolization success was comparable for Onyx and PHIL, pause time had a considerable effect on the embolization success in an in vitro AVM model. Compared with Onyx, lower volumes of PHIL were required for the same extent of embolization.
Published online July 12, 2017
Gesehen am 06.08.2018